Power scaling and mode quality of an acetylene mid-infrared hollow-core optical fiber gas laser - Weerasinghe, Hewa Walpitage Kushan Madushanka (Kansas State University, 2019)
This thesis explores the power scalability and the mode quality of mid-IR acetylene filled Hollow-core Optical Fiber Gas LASer (HOFGLAS). The mid-IR lasing mechanism is based on the population inversion in acetylene molecules within the hollow-core of the hypocycloidal kagome structured fiber. The acetylene gas is optically pumped with 1 ns pulses near 1.5 µm using an optical parametric amplifier (OPA). The acetylene molecules absorb pump light via rotational-vibrational overtone transitions and can lase in 3 µm region through dipole allowed transitions. Since hollow-core fiber provides long interaction length and tight confinement for gas and light, higher gain is achieved by single pass configuration. In this work, the effect of fiber length, gas pressure, pump wavelength, and pump pulse duration on the mid-IR laser is experimentally studied in order to scale the laser system to higher mid-IR energies. By studying combinations of fiber length with different acetylene gas pressures, we were able to remove the laser signal saturations that have been observed in previous studies. Furthermore, the produced mid-IR laser energy linearly depends on the absorbed near-IR pump energy, and it is only limited by the available near-IR pump energy. Moreover, the highest mid-IR pulse energy of 2.56 µJ is measured when the acetylene filled HOFGLAS system is pumped via the P(9) line, which is the highest ever mid-IR pulse energy that has been measured to our knowledge. Mid-IR laser efficiency is independent of acetylene gas pressure and for the gas pressure region we worked on, a shorter pump pulse width is preferred. An experiment is designed and performed based on the M² to study the beam quality of the produced mid-IR beam. The mid-IR laser output shows near diffraction-limited performance with an M² value of 1.15. Finally, a numerical model based on the saturated absorption for inhomogeneous line profile is proposed to estimate the absorbed near-IR pump energy only by acetylene gas.
Keywords: Gas laser; Fiber laser; Mid-IR laser; Hollow-core fiber